Islam dan Modernitas dalam Pandangan Fethullah Gulen - Sehat Ihsan Shadiqin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Phobia and prejudice toward Islam in America and Europe are contributed by a small particular group that name their violence and movement on behalf of Islam. In fact, Islam is a religion that calls for peace and harmony. But these impressions are still inadequate to purify the image of Islam. It requires to systematic effort to show that the truth teaching of Islam that guarantees and supports the universal values of mankind to life in peace and harmony. Fethullah Gulen, who is scholar, a preacher, a sufi, a teacher and is a Muslim activist from Turkey, is one of scholars and actors how has done this mission. Currently, Gulen has tens million followers from around the world that bring about to become one of the most influential person in contemporary Muslim world. This papers seeks to see the basic and model of religious social movement that are done by Fethullah Gulen in his campaign in cosmopolitan society. The campaign strongly states that Islam is very relevant to modern life. The papers specifically answers three fundamental questions; how does Gulen interpret scare texts of Islamic teaching? What model of interpretation that Gulen employs in understanding various dimensions of Islamic Teaching? How the normative concepts of Fethulllah Gulen’s Teaching used to spread Islamic teaching